2003
DOI: 10.1076/ceyr.27.5.289.17220
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of invasive and cytotoxic Pseudomonas aeruginosa strain-induced corneal disease responses to therapeutics

Abstract: Differences between invasive and cytotoxic strain infections in their early response to the different therapeutic regimens did not translate to notable differences after 7 days, but the effects of antibiotics in halting disease progression were delayed for both strain types. These results suggest that successful management might be improved by addressing factors contributing to disease progression during sterilization of the cornea by antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 16 publications
5
34
1
Order By: Relevance
“…As we know, steroid application has been used to promote cornea infection by bacteria, fungi, viruses, and acanthamoebae in animal models. [36][37][38][39] It seems that our present results are opposed to the in vivo findings. However, in cornea infection in animal models the epithelial integrity has always been breached.…”
Section: Discussioncontrasting
confidence: 64%
“…As we know, steroid application has been used to promote cornea infection by bacteria, fungi, viruses, and acanthamoebae in animal models. [36][37][38][39] It seems that our present results are opposed to the in vivo findings. However, in cornea infection in animal models the epithelial integrity has always been breached.…”
Section: Discussioncontrasting
confidence: 64%
“…Neutrophils are the predominant infiltrating cell-type in lung infections, and it has been proposed that killing of infiltrating neutrophils creates an immunocompromised milieu in the lung in which P. aeruginosa can thrive (31). We and others reported that infection with either ExoU or ExoS expressing strains cause keratitis in murine models, and that bacterial clearance and the severity of infection is dependent on the innate immune response, including neutrophil infiltration to the corneal stroma and bacterial survival (7-9, 11, 26). The obvious importance of neutrophils in clearing P. aeruginosa infections, both in the lung and in the eye, and the identification of neutrophils as the primary target of type III secretion in the lung model of infection, prompted us to revisit the role of type III secretion in eye infections, particularly for ExoS-producing strains of P. aeruginosa .…”
mentioning
confidence: 96%
“…ExoS- and ExoU-expressing isolates are recovered from infected corneas at similar frequencies (24). In corneal infections, type III secretion appears to be important for ExoU-producing, cytotoxic variants of P. aeruginosa (25), whereas ExoS-producing strains did not depend on type III secretion to cause disease (26-28). This observation was curious in that lack of ExoT, which is produced by both ExoU and ExoS producing strains of P. aeruginosa , only had a virulence phenotype in the ExoU producing, but not the ExoS producing strain (28).…”
mentioning
confidence: 99%
“…The resistance rate increased from 19% to 52% in 3 years 23. Regarding aminoglycosides, they were found to be less effective than ciprofloxacin in eradicating invasive P. aeruginosa strains 24. In ciprofloxacin-resistant P. aeruginosa , susceptibility rate for tobramycin was only 67% 25.…”
Section: Discussionmentioning
confidence: 99%